THE IMPACT OF INTERNAL MARKETING PRACTICE ON STUDENT AMBASSADOR’S ENGAGEMENT IN CICIL.CO.ID - Nugroho, Stefanus Febri Adi; Chaerudin, Rendra (Journal of Business and Management, 2017)
Abstract. Engaging younger worker is one of the phenomena of concern to organizations and companies. That makes companies’ interests in employing younger worker like students as their brand ambassadors is on the rise. One of practice that could affect employee engagement is internal marketing. Cicil.co.id, an Indonesian startup wants to know the impact of internal marketing practices on their student ambassador program. This research aims to analyze the impact of internal marketing practice on student ambassadors’ engagement in Cicil and develop a model to improve current internal marketing strategy. A quantitative research was conducted on 65 Cicil student ambassadors. Simple linear regression method was used to measure the significance of internal marketing practices influence on engaged behavior of student ambassador. Variable dimension analysis was conducted to evaluate current internal marketing practice and develop a model as a guideline to improve Cicil’s internal marketing strategy. Internal marketing practices at Cicil is proved to have a positive and significant impact on engaged student ambassadors’ behavior. A model based on the internal marketing dimension was constructed to be guideline for planning internal marketing strategy. Conclusion: Internal marketing practices have a significant impact on engaged behavior. Keywords: Employee Engagement, Engaged Behavior, Internal Marketing, Student Ambassador